1919 Me. Acts 193 - (:unkn) unknown (My University, 1919)
Possession of loaded shotgun or rifle in motor vehicle on highways, fields or forests prohibited; penalty: No person shall have a rifle or shotgun, either loaded or with a cartridge in the magazine thereof, in or on any motor vehicle while the same is upon any highway or in the fields or forests. Whoever violates any provision of this section shall be subject to a penalty of not more than one hundred dollars and costs for each offense or imprisonment for not more than sixty days or both said fine and imprisonment in the discretion of the court.
Keywords: VEHICLES